Empowering Women in Fishing Villages: The Impact of Community Guidance on Social Support, Resource Access, and Cultural Change - Erdiyanti, Yucky Putri; Rusmana, Nandang; Saripah, Ipah; Pratama, Finsa Muhammad (Universitas Negeri Padang, 2024)
This study investigates the impact of the Community Guidance Model on women’s empowerment in the fishing village of Nelayan, Pangandaran Regency, Indonesia. It explores how this model promotes gender equality by enhancing social support, improving resource access, and driving cultural change. Using a qualitative case study approach, the research focuses on women participating in the community guidance program, selected through purposive sampling. Data collection methods included in-depth interviews, participant observations, and analysis of program documents. Thematic analysis revealed that the Community Guidance Model significantly strengthens social support networks, grants women greater access to economic and educational resources, and fosters a shift in cultural norms that traditionally limit women’s roles. These changes enable women to take on active roles within their communities, enhancing both their welfare and social standing. The study concludes that the Community Guidance Model is an effective strategy for empowering women in fishing villages, offering a pathway to sustainable gender equity and social inclusion. These findings support the expansion of such programs to achieve lasting improvements in the well-being and agency of women across Indonesian coastal communities.